Chagas disease and SARS-CoV-2 coinfection does not lead to worse in-hospital outcomes - Molina, Israel (2021)
PROSICS Barcelona, Vall d’Hebron University Hospital, Passeig de la Vall d’Hebron. Barcelona, Spain / Fundação Oswaldo Cruz. Instituto René Rachou. Belo Horizonte, MG, Brazil.